A new approach to estimating the natural rate of interest - Luca Benati (University of Bern, Department of Economics, 2022)
Building upon the insight that M1 velocity is the permanent component of nominal interest rates - see Benati (2020) - I propose a novel, and straightforward approach to estimating the natural rate of interest, which is conceptually related to Cochrane's (1994a) proposal to estimate the permanent component of GNP by exploiting the informational content of consumption. Under monetary regimes (such as inflation-targeting) making inflation I(0), the easiest way to implement the proposed approach is to (i) project the monetary policy rate onto M1 velocity-thus obtaining an estimate of the nominal natural rate-and then (ii) subtract from this inflation's sample average (or target), thus obtaining the real natural rate. More complex implementations based on structural VARs produce very similar estimates. Compared to existing approaches, the one proposed herein presents two key advantages: (1) under regimes making inflation I(0), M1 velocity is equal, up to a linear transformation, to the real natural rate, so that the natural rate is, in fact, observed; and (2) based on a high-frequency estimate of nominal GDP, the natural rate can be computed at the monthy or even weekly frequency. In the U.S., Euro area, and Canada the natural rate dropped sharply in the months following the collapse of Lehman Brothers. Likewise, the 1929 stock market crash was followed in the U.S. by a dramatic decrease in the natural rate.
Keywords: 330; Natural rate of interest; money velocity; structural VARs; unit roots; cointegration